Тепловая неустойчивость слоистой вязкоупругой прямоугольной призмы при высокочастотном сжимающем нагружении - Доля, Е.В.; Червинко, О.П.; Сенченков, И.К. (Прикладная механика, 2010)
Within the framework of coupled problem of thermoviscoelasticity and basing on the finite element modeling, the thermal instability under vibrational heating of the rectangular prism is studied. The prism is formed of cooper and polystyrene (PS) or polymetylmetacrylate (PMMA) layers and is subjected of high-frequency force or kinematic compression. It is established that in the case of PS the thermal instability is occurring for the force loading and is absent for the kinematic one, whereas in the case of PMMA the thermal instability is occurring for doth cases of loading. It is revealed that the dissipation mechanism is changed on the volume one in the neighbourhood of the softening tempera- ture, what is the determining factor for sufficiently thin polymer layers. Dynamics effects on the load critical parameters quantitatively and qualitatively. В рамках зв’язаної задачі термов’язкопружності на основі скінченно-елементного
моделювання вивчено теплову нестійкість при вібророзігріві прямокутної призми, яка складається з
мідних і поліетиленових або поліметилметакрилатових шарів. Призма піддається високочастотному
силовому або кінематичному стиску. Встановлено, що у випадку поліетилену термічна нестійкість має
місце за умови силового навантаження і відсутня при кінематичному, а у випадку поліметилме-
такрилату нестійкість має місце в обох випадках навантаження. Це пов’язується з наявністю ділянок
зростання з температурою зсувної і об’ємної податливостей втрат для кожного з полімерів. Виявле-
но, що в околі температури перетворень зсувний механізм дисипації замінюється на об’ємний, якиї є
визначальним для достатньо тонких полімерних шарів. Динамічність якісно і кількісно впливає на
критичні значення параметрів навантаження.